A two-stage probabilistic approach for the risk assessment of submarine landslides induced by gas hydrate exploitation. (June 2020) - Chen, Yangming; Zhang, Lulu; Liao, Chencong; Jiang, Mingjing; Peng, Ming
Abstract: In this paper, a two-stage risk assessment approach for gas hydrate exploitation is presented. In the first stage, a probabilistic analysis method is used to evaluate the failure probability of submarine landslide due to hydrate exploitation. The excess pore pressure due to hydrate exploitation is evaluated using a proposed maximum excess pore pressure model, which can consider the equilibrium of pressure and temperature for hydrates during decomposition. An infinite slope stability analysis and Monte Carlo simulations are then used to evaluate the failure probability of the slope with consideration of the generated excess pore pressure. In the second stage, a Bayesian network model to estimate the mortality rate of platform workers is proposed based on the logical sequence of events. The proposed approach is easy to implement and provides an efficient approach for quantitative assessment of human risk. Application of the proposed approach to a potential hydrate exploitation area, the Shenhu area in the South China Sea, is presented. The probabilistic analyses reveal that the production temperature T 1 and the slope angle β have significant influences on the failure probability. Analysis of the human risk suggests that the key factors affecting the mortality rate are the distance of the platform to landslide and the equipment time for the workers to equip with lifejackets.